Spectroscopic characterization of lithium combustion. Issue 1644 (14th March 2014) - Brockhinke, Andreas; Koppmann, Julia; Brockhinke, Regina; Kellermann, Renate; Eckert, Helmut; Taroata, Dan; Schmid, Guenter
ABSTRACT In this work, the exothermic reaction of the chemical energy storage material for stranded renewable energy, lithium is analyzed in carbon dioxide (CO2) and air. Spectroscopic techniques were used to characterize the reaction of bulk lithium pellets of up to 1 g weight. In comparison, power plant applicable combustion of atomized lithium spray was analyzed. Electrical high voltage spark was used to overcome to activation energy of the combustion for the experiments with bulk lithium. The lithium spray was successfully ignited by pre-heating the reaction gases (air and CO2). Radiation temperature of the bulk lithium during reaction in air was calculated to 2260 K. The observed green and red emission of the lithium combustion could be demonstrated in the spectral analysis. In CO2 atmosphere the reaction products were found to be lithium carbonate with little lithium oxide. Beside, lithium carbide could be detected in the reaction product of the combustion of bulk lithium. The gaseous reaction product carbon monoxide (CO), which could be further converted with hydrogen from renewable sources to valuable methanol or gasoline, was detected online by gas analysis.